Strengthening Ombudsman Authority in Recommendation Implementation: An Analysis of Public Service Accountability - Dyah Adriantini Sintha Dewi; Fadil Muhammad; Dilli Trisna Noviasari; Prihatin Dwihantoro (International Journal of Law and Society, 2026)
Although the Ombudsman of the Republic of Indonesia (ORI) is legally authorised to supervise public services and issue recommendations to address maladministration, the implementation of those recommendations remains inconsistent, revealing a gap between their normative binding force and their practical enforceability. This study aims to analyse the normative construction and weaknesses of the legal framework governing the implementation of ORI recommendations under Law No. 37 of 2008 on the Ombudsman of the Republic of Indonesia, Law No. 25 of 2009 on Public Services, and Law No. 23 of 2014 on Regional Government, and to formulate policy directions for strengthening ORI's authority. This research employs normative juridical research using statute, conceptual, and comparative approaches. The study employs primary, secondary, and tertiary legal materials, supplemented by official Ombudsman reports, and examines them through argumentative legal reasoning and norm–implementation gap analysis. The findings show that the main weakness lies not in the absence of legal recognition of ORI recommendations, but in the weak executorial design, indirect sanction mechanisms, fragmented follow-up responsibilities, and defensive bureaucratic culture that undermine compliance. Lawrence M. Friedman's legal system theory reveals that these weaknesses arise from problems in legal substance, structure, and legal culture. At the same time, Institutional Reputation Theory shows that concerns over credibility, trust, legitimacy, and symbolic exposure also influence compliance. This study concludes that strengthening ORI requires clearer executorial follow-up mechanisms, harmonised inter-institutional responsibilities, stronger sanction activation, and reputationally responsive compliance strategies. Although limited to normative analysis, this article offers originality by integrating legal system analysis and institutional reputation to explain the enforcement gap of ORI recommendations.